Critical Review of Halal Industry Policy in Indonesia - Lutfi, Chairul (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
Indonesia, with the world's largest Muslim population, has seen significant growth in its halal industry driven by increasing awareness of Islamic ethical values and government initiatives. However, the regulatory framework governing halal certification remains fragmented and complex, leading to implementation challenges and legal uncertainty. This study critically examines Indonesia's halal industry policies, focusing on the Halal Product Assurance (JPH) Law and its alignment with Islamic principles of halal (permissible) and thayyib (wholesome). Employing a qualitative approach, this study analyzes legal documents and the existing literature to identify regulatory overlaps, institutional inefficiencies, and barriers for small and medium enterprises. The findings highlight the need for harmonization of regulations, clarity on the validity period of halal certificates, and improved coordination among government agencies. The study also evaluates the effectiveness of policies in achieving compliance, consumer trust, and socioeconomic benefits, revealing persistent gaps and inconsistencies in enforcement. By contextualizing the JPH framework within Gustav Radbruch's legal philosophy, this study underscores the importance of balancing legal certainty, expediency, and justice. The study concludes that comprehensive improvements in Indonesia's halal industry policies have the potential to enhance consumer confidence, product competitiveness, and the country's position as a global halal industry hub, while emphasizing the need for further empirical research to refine the understanding of the underlying Islamic values and sociocultural dynamics.